2018
DOI: 10.1152/ajprenal.00515.2017
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the B splice variant of NBCe1 (SLC4A4) in the mouse kidney

Abstract: Sodium-coupled bicarbonate transporters are critical for renal electrolyte transport. The electrogenic, sodium-coupled bicarbonate cotransporter, isoform 1 (NBCe1), encoded by the SLC4A4 geneencoded by the SLC4A4 gene has five multiple splice variants; the A splice variant, NBCe1-A, is the primary basolateral bicarbonate transporter in the proximal convoluted tubule. This study's purpose was to determine if there is expression of additional NBCe1 splice variants in the mouse kidney, their cellular distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 62 publications
4
25
0
Order By: Relevance
“…We have recently identified that NBCe1, a basolateral proximal tubule Na ϩbicarbonate cotransporter, regulates proximal tubule ammonia metabolism (18,31). Two splice variants of NBCe1, NBCe1-A and NBCe1 variant B (NBCe1-B), are present in the kidney (9,31). We have previously shown that there are no significant sex differences in NBCe1 expression under basal conditions (20).…”
Section: F893mentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently identified that NBCe1, a basolateral proximal tubule Na ϩbicarbonate cotransporter, regulates proximal tubule ammonia metabolism (18,31). Two splice variants of NBCe1, NBCe1-A and NBCe1 variant B (NBCe1-B), are present in the kidney (9,31). We have previously shown that there are no significant sex differences in NBCe1 expression under basal conditions (20).…”
Section: F893mentioning
confidence: 99%
“…Two of these variants are expressed in the kidney. The A variant is expressed at high levels in the renal proximal tubule basolateral plasma membrane, whereas the B variant is expressed in the mouse renal proximal tubule at apparently much lower levels (9). Thus, we next evaluated the NBCe1-A response to acid loading.…”
Section: F893mentioning
confidence: 99%
“…Finally, in reference to a recent report of Nbce1b expression in the renal medulla, 9 the ability of the kidneys to maintain an apparently appropriately elevated plasma [HCO 3 2 ] does…”
Section: The Role Of Renal Nbce1bmentioning
confidence: 99%
“…, either to maintain intracellular pH (e.g., in neurons) or to support transepithelial anion/fluid secretion (e.g., in gastrointestinal epithelia). [7][8][9] NBCe1-A and NBCe1-B/C differ not only in their distribution but also in their Nt and Ct sequences; NBCe1-A includes a unique 41 amino-acid autostimulatory domain (encoded by the orange section of exon 4 in Figure 1A), whereas NBCe1-B/C include in its place an 85 amino-acid autoinhibitory domain (encoded by exons 2 and 3; blue in in Figure 1A). 10 The consequence of these alternative Nt sequences is that NBCe1-A exhibits a greater conductance than NBCe1-B/C.…”
mentioning
confidence: 99%
“…Three variants, NBCe1-A, NBCe1-B and NBCe1-C, are present in both humans and in rodents, and two, NBCe1-D and NBCe1-E, have to date been identified only in rodents. Only two of these variants, NBCe1-A and NBCe1-B appear to be expressed in the kidney (74,75) . NBCe1-A is the more highly expressed of the two, and is found exclusively in cortical proximal tubule segments, whereas…”
Section: Regulation By Nbce1mentioning
confidence: 99%